Research results motivate student learning - Ivanchenko, E. Z.; Malakhova, S. N.; Melnikova, O. Z.; Іванченко, Олена Зенонівна; Малахова, Світлана Миколаївна; Мельнікова, Оксана Зенонівна (Czech Republic, Karlovy Vary: Skleněný Můstek, 2017)
In the effectiveness of the educational process, the motivation of students plays a leading role, which is a complex and multilevel phenomenon. According to modern concepts of pedagogy and psychology, motivation is a collection of various factors, that determine the behavior and activities of a person. The general structure of educational motivation forms the meaning, the need for training, the goals, interests, desires of a person.